2022
DOI: 10.1093/brain/awac293
|View full text |Cite
|
Sign up to set email alerts
|

‘Hippocampal innate inflammatory gliosis only’ in pharmacoresistant temporal lobe epilepsy

Abstract: Drug-resistant mesial temporal lobe epilepsy is a devastating disease with seizure onset in the hippocampal formation. A fraction of hippocampi samples from epilepsy-surgical procedures reveals a peculiar histological pattern referred to as ‘gliosis only’ with unresolved pathogenesis and enigmatic sequelae. Here, we hypothesize that ‘gliosis only’ represents a particular syndrome defined by distinct clinical and molecular characteristics. We curated an in-depth multiparameter integration of syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…After full text screening, 15 cohort studies with 2485 patients were included in the meta-analysis of seizure outcomes. [14][15][16]18,20,[41][42][43][44][45][46][47][48][49][50] Seven articles including six cohorts with detailed information of postoperative memory outcome were included. 14,[17][18][19][20]50,51 Eight studies were conducted from four datasets , 16,18,19,44,46,[51][52][53] and only the larger cohort study reporting seizure outcomes was included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After full text screening, 15 cohort studies with 2485 patients were included in the meta-analysis of seizure outcomes. [14][15][16]18,20,[41][42][43][44][45][46][47][48][49][50] Seven articles including six cohorts with detailed information of postoperative memory outcome were included. 14,[17][18][19][20]50,51 Eight studies were conducted from four datasets , 16,18,19,44,46,[51][52][53] and only the larger cohort study reporting seizure outcomes was included.…”
Section: Resultsmentioning
confidence: 99%
“…Inconsistent postoperative seizure and cognitive outcomes among different subtypes were reported. [14][15][16][17][18][19][20] Therefore, we performed a systematic review and meta-analysis to consider the total body of evidence and comprehensively assess postoperative seizure and memory outcome in different HS subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, six possible research directions were identified as follows ( Figure 8A ): “mechanism of excitotoxicity induced by glutamate and neuroprotection by glutamate transporters,” “the modulating mechanism of synaptic transmission by glutamate receptors,” “AEDs,” “animal models study of epileptogenesis in TLE,” “autoimmune diseases associated with seizures and epilepsy,” and “ in vivo studies.” The common keywords with the most occurrences were “epilepsy,” “glutamate,” “TLE,” “hippocampus,” and “seizures.” TLE is one of the most common types of DRE ( Engel et al, 2012 ). The sclerotic hippocampus is key in generating and maintaining temporal lobe seizures ( Grote et al, 2022 ). The hippocampus is an important region for studying the pathological mechanisms of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…TLE is one of the most common types of DRE (Engel et al, 2012). The sclerotic hippocampus is key in generating and maintaining temporal lobe seizures (Grote et al, 2022). The hippocampus is an important region for studying the pathological mechanisms of epilepsy.…”
Section: Figure 4dmentioning
confidence: 99%
“…Thus, these alterations represent disease modifiers with respect to network function rather than primary epileptogenic alterations. In contrast, LE-like and "gliosis only" alterations may constitute seizure foci and harm neuronal network function, 54,55 manifesting as poor neuropsychological performance.…”
Section: Neuropathologymentioning
confidence: 99%